Near-infrared (NIR) fluorescence-emitting small organic molecules for cancer imaging and therapy. (13th October 2022) - Li, Hui; Kim, Yujun; Jung, Hyoje; Hyun, Ji Young; Shin, Injae
Abstract : We discuss recent advances made in the development of NIR fluorescence-emitting small organic molecules for tumor imaging and therapy. Abstract : Near-infrared (NIR) fluorophores have unique features that endow them with several advantages over conventional shorter wavelength emitting dyes. As a result, they have been widely utilized as fluorescence and photoacoustic imaging agents, as well as photodynamic and photothermal therapeutic agents. However, non-targeting NIR fluorescence-emitting organic molecules have the drawback of low selectivity toward tumors, which potentially results in severe side effects caused by damage to normal tissues. Thus, the development of NIR fluorophore-based substances that target tumors is a highly active area in medicinal chemistry research. Research efforts carried out thus far have led to the development of a number of NIR fluorophore-based, tumor imaging and therapeutic agents. The discussion in this review focuses on the results of research reported in the 2012–2021 period, giving particular emphasis to studies of NIR small organic dye-based imaging and therapeutic agents that are designed utilizing cancer-selective strategies.